2020
DOI: 10.1002/cncr.32708
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in patients with cancer

Abstract: Seizures are common in patients with cancer and either result from brain lesions, paraneoplastic syndromes, and complications of cancer treatment or are provoked by systemic illness (metabolic derangements, infections). Evaluation should include a tailored history, neurologic examination, laboratory studies, neuroimaging, and electroencephalogram. In unprovoked seizures, antiepileptic drug (AED) treatment is required, and a nonenzyme‐inducing AED is preferred. Treatment of the underlying cancer with surgery, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 93 publications
(183 reference statements)
0
18
0
5
Order By: Relevance
“…Seizures lead to the initial presentation of 20-40% of patients with glioma (more common in IDH-mutant gliomas). 10,11 On the other hand, seizures are rare in MS; a pooled analysis of 39 studies found the prevalence of seizures and epilepsy in MS patients to be 2% and 3%, respectively. 12 As with MS, gliomas may cause focal neurologic deficits depending on the size and location of the tumor and on the amount of vasogenic edema.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures lead to the initial presentation of 20-40% of patients with glioma (more common in IDH-mutant gliomas). 10,11 On the other hand, seizures are rare in MS; a pooled analysis of 39 studies found the prevalence of seizures and epilepsy in MS patients to be 2% and 3%, respectively. 12 As with MS, gliomas may cause focal neurologic deficits depending on the size and location of the tumor and on the amount of vasogenic edema.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Moreover, seizures may occur in patients with many types of cancer, including in those without brain lesions. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system malignancies cause seizures in 35%–70% of patients, who often present with resistance to antiepileptics 15 . Moreover, seizures may occur in patients with many types of cancer, including in those without brain lesions 16 …”
Section: Introductionmentioning
confidence: 99%
“…During their illness, many patients who have cancer experience seizures, with the incidence varying according to the type of tumor. Low-grade gliomas (LGG) ranked third among them 14 . Although LGG (astrocytomas, oligodendrogliomas, and oligoastrocytomas) are considered relatively benign, well-differentiated tumors and have 5-year survival rates of 59.9%, approximately 70% of LGG patients develop GBM within 5–10 years 15 .…”
Section: Introductionmentioning
confidence: 99%